Penggambaran Individualisme Dalam Drama Korea Happiness - Wardani, Fransiska Nikola Cahya (Peneliti.net, 2024)
This study explores the impact of individualism in society, focusing on the Korean drama Happiness. The drama revolves around a hazardous illness that spreads throughout the city, leading to a regional quarantine. The study examines 22 scenes using John Fiske's semiotics at reality, representation, and ideology levels. It reveals that individualism is portrayed as all sources of need are considered private property in society, a focus on achievement and self-actualization, independent living and placing a high value on freedom, relying on media for information, pursuing one's own interests in work, and becoming tech savvy. The negative effects of individualism can therefore be perceived as being selfish, not caring about others, passing judgment on those who have come into contact with infected individuals, being unable to socialize with others, and believing oneself to be always correct. Being capable of being independent and confident has a favorable impact. Meanwhile, individualism, patriarchy, and class are the ideologies present in this drama.